UTILIZING LEARNING POTENTIAL PROACTIVE STRATEGIES STUDENT MOTIVATION AND INTEREST IN LEARNING - Hura, Delfita; Mendrofa, Erlin Talenta; Gulo, Bezisokhi; Riana, Riana (Universitas Islam Raden Rahmat Malang, 2024)
This research was conducted qualitatively with a descriptive approach. Descriptive qualitative methods. To collect data by making direct observations in the classroom. Techniques and data collection use reduction, data presentation and data verification. In this research, the research subjects are students. The research object investigated is an effort to increase student interest and motivation. In this research, the teacher monitors the level of student activity using an observation sheet which has five different indicators. The observation results showed that the level of attention reached 62.50% of the maximum score, while the level of cooperation and social relations was 37.50%. Apart from that, 50.00% of students were also active in expressing opinions or ideas, while their problem solving ability reached 41.67%. The last indicator, namely discipline, reaches 50.00% of the maximum score